A 'conversation' between Frank Land (FL) and Antony Bryant (AB): PART I. (December 2020) - Bryant, Antony; Land, Frank
The 'conversation' offers an important contribution to the archaeology of information systems, both in practice as an academic domain or discipline, and a focus on the genealogy of the field, including some of the accidents and deviations that marked later developments. It is derived from a series of conversations and later exchanges that I arranged with Frank Land. The substantive aspects date from the late 2017 and were then developed in a series of exchanges in 2018; although in effect he and I have been developing this conversation over many years, during which he has been continually challenging, expansive and forthcoming. Comments forthcoming from readers of earlier drafts indicated some perplexity regarding the genre and the objectives of our contribution, so it is important to note that the term 'conversation' is something of a conceit. It is not an interview per se, nor is it a biographical account. The core of what follows developed from our verbatim exchanges both face-to-face, and later via email. Some sections, however, have been reworked and enhanced to clarify and augment the issues raised. In addition, we have sought to provide a good deal of background and narrative to guide readers through the text, offering pointers to further resources. The overall contribution is intended to provide an informed and, we hope, informative contribution to people's understanding of key social and technical issues of our time.